Herbal, Homeopathic and Hormonal Therapy Improves Macromineral Profile and Fertility Outcomes in Postpartum Anestrus Buffaloes - Kumar, A.; Kumar, R.; Kumar, R.; Srivastava, S.; Kumar, P.; Verma, H. (The Indian Journal of Animal Reproduction, 2021)
The study was aimed to assess the effect of Aegle marmelos (Indian Bael), Oophorinum and Progesterone on serum calcium, phosphorus and fertility outcomes. A total of 24 postpartum anestrous buffaloes were randomly allocated in 4 groups as T0, T1, T2 and T3; each group comprised of six animals. All the animals were dewormed with fenbendazole (10mg/kg) before commencement of experiment. The T0 (untreated control) buffaloes were supplemented with mineral mixture (50 gm daily for 10 days). In addition to mineral mixture, the T1, T2 and T3 buffaloes were treated with Aegle marmelos, Oophorinum and progesterone hormone, respectively. The serum calcium and phosphorus values was significantly (P<0.05) increased after therapy in Oophorinum treated buffaloes as compared to other groups. The estrus induction response was 50, 100 and 33.33% in Aegle marmelos, Oophorinum and Progesterone treated groups, respectively. Among responded animals, the overall conception rate after three inseminations was 0, 66.66, 83.33 and 100%, respectively for T0, T1, T2 and T3 groups. In conclusion, herbal and homoeopathic therapeutics can be used effectively to manage clinical syndrome of post-partum anestrus in Buffaloes.